Atendimento às mulheres vítimas de violência doméstica na Regional de saúde do Paraná - Vasconcelos, Rita de Kátia Ottes (2021)
The network of care for women victims of domestic violence is composed of several services in which multiprofessional care is offered, in which it is expected to develop an interdisciplinary work in order to materialize intersectoriality. In this sense, we have, as a general objective, to describe the care provided to women victims of domestic violence in the cities covered by the 10th Health Regional Office of the State of Paraná. To this end, a quantitative and qualitative research was developed, in the period from April to September 2020, through a documentary search of Notifications of Domestic Violence on the site of the National Registry of Health Establishments of the Department of Public Safety of Paraná, as well as in the Information System of Notifiable Diseases. Furthermore, 22 semi-structured interviews were carried out with managers, primary care directors, and professionals who assist victims of domestic violence in 22 of the 25 cities in the 10th Health Regional Office of Paraná. The data were analyzed using descriptive statistics and content analysis. It was identified that all municipalities have a police station, family health units, basic health units, and only one has a women's police station. Of the domestic violence notifications, between 2015 and 2020, 5912 notifications were obtained. Of the professionals who were interviewed, 21 were female, aged between 26 and 60 years, 10 were nurses, and 18 had postgraduate degrees. The speeches of the professionals were organized into pre-established categories according to the questions in: Perception of the professional about domestic violence and regarding the care of women victims of domestic violence in the municipality; Services Flow and operation of the services of the municipality that provide care to women victims of domestic violence; Facilities and difficulties encountered in the care of women victims of domestic violence in their municipality and health region; Perception of the professional regarding the resolutivity of the services in the care of women victims of domestic violence. This research can indicate that the assistance to women victims of domestic violence in the Paraná Regional Office is diversified by the established flow, the size of the municipality, the existing network of services, as well as the available team. It was observed that there is a taboo and prejudice in relation to domestic violence seen as materialization of patriarchal power and the lack of knowledge of the rights inherent to this population, however, the service is offered within the existing possibilities, it is believed to be necessary to improve the implementation of public policies that can contribute to the managers, coordinators of Primary Care and professionals who assist women victims of domestic violence, seeking new and different ways to meet this demand in a perspective of change in everyday life in order to improve the work already done.